Notes—An Index of Health: An Application in Accidents - Krall, John Morton (Management Science, 1972)
This paper presents an index of health which is based on a multiple decrement model. The index is denned in terms of costs and benefits which are weighted sums of losses and gains experienced in a population due to poor or good health. The index of health is then applied to a farm accident problem. The purpose of the index is to serve as an aid to administrators in making decisions concerning which types of accidents should receive larger resource allocations in the effort toward elimination.